Cardiovascular Screening for the Asymptomatic Patient with Diabetes: More Cons Than Pros - Konstantinos Makrilakis; Stavros Liatis (Journal of Diabetes Research)
Diabetes mellitus is associated with an increased risk of coronary heart disease (CHD) morbidity and mortality. Although it frequently coexists with other cardiovascular disease (CVD) risk factors, it confers an increased risk for CVD events on its own. Coronary atherosclerosis is generally more aggressive and widespread in people with diabetes (PWD) and is frequently asymptomatic. Screening for silent myocardial ischaemia can be applied in a wide variety of ways. In nearly all asymptomatic PWD, however, the results of screening will generally not change medical therapy, since aggressive preventive measures, such as control of blood pressure and lipids, would have been already indicated, and above all, invasive revascularization procedures (either with percutaneous coronary intervention or coronary artery bypass grafting) have not been shown in randomized clinical trials to confer any benefit on morbidity and mortality. Still, unresolved issues remain regarding the extent of the underlying ischaemia that might affect the risk and the benefit of revascularization (on top of optimal medical therapy) in ameliorating this risk in patients with moderate to severe ischaemia. The issues related to the detection of coronary atherosclerosis and ischaemia, as well as the studies related to management of CHD in asymptomatic PWD, will be reviewed here.